2023
DOI: 10.3961/jpmph.22.417
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Tobacco Smoking and Dental Caries in the Indonesian Population: Results of a National Study in 2018

Abstract: Objectives: The 2018 Basic Health Research (RISKESDAS), conducted by the Ministry of Health of the Republic of Indonesia showed a high prevalence of dental caries (88.8%) in Indonesia and suggested that smoking tobacco was associated with an increased risk of dental caries. This study analyzed the association between tobacco smoking and dental caries in the Indonesian population.Methods: This was a cross-sectional analysis of secondary data collected from RISKESDAS 2018. The study population included 35 391 In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…O tabagismo além de ser um hábito altamente nocivo a nível sistêmico com potencial carcinogênico, pode desencadear ou agravar a infecção de carie em seus consumidores 25 . Um estudo mostrou que, a cárie dentária não tratada e a perda dentária são comumente encontradas em pacientes tabagistas, com grandes variações entre diferentes países, faixas etárias e status socioeconômico 26 .…”
Section: Revisão De Literaturaunclassified
“…O tabagismo além de ser um hábito altamente nocivo a nível sistêmico com potencial carcinogênico, pode desencadear ou agravar a infecção de carie em seus consumidores 25 . Um estudo mostrou que, a cárie dentária não tratada e a perda dentária são comumente encontradas em pacientes tabagistas, com grandes variações entre diferentes países, faixas etárias e status socioeconômico 26 .…”
Section: Revisão De Literaturaunclassified
“… 6 There were studies demonstrated that smoking was associated with an increased risk of dental caries. 7 , 8 In addition, the results of a study in children showed that compared with the control group, the decayed, missing and filled tooth (DMFT) score, the colonization amount of Streptococcus mutans and Lactobacillus in saliva were increased, and the pH value, flow rate and buffer capacity of saliva were decreased in passive smoking children. 9 This may be due to increased tooth adhesion by Streptococcus mutans , an important cariogenic bacterium metabolizing sucrose in the presence of nicotine.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent article published in this journal, the authors identified tobacco use as a significant contributor to the increasing incidence of dental caries among people in Indonesia [ 1 ]. Tobacco use is currently a major global public health problem, causing the direct and indirect deaths of over 8 million people yearly.…”
mentioning
confidence: 99%